2007
DOI: 10.1111/j.1398-9995.2006.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Extent, patterns, and burden of uncontrolled disease in severe or difficult‐to‐treat asthma

Abstract: This study demonstrated that few severe or difficult-to-treat asthma patients achieved control over a 2-year period and the economic consequence of uncontrolled disease is substantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 27 publications
5
105
2
2
Order By: Relevance
“…Also, a higher ATAQ score (more control problems) was associated with lower quality of life in subjects with asthma, indicated by generic and diseasespecific quality of life measures, such as the SF-36, the standardized version of the Asthma Quality of Life Questionnaire, 12 and the Mini Asthma Quality of Life Questionnaire. 55,68 Furthermore, a strong correlation and similar performance were reported between the ATAQ and the ACT at home and in clinical settings (r ϭ Ϫ0.73). 25,69,70 …”
Section: Validitysupporting
confidence: 59%
See 1 more Smart Citation
“…Also, a higher ATAQ score (more control problems) was associated with lower quality of life in subjects with asthma, indicated by generic and diseasespecific quality of life measures, such as the SF-36, the standardized version of the Asthma Quality of Life Questionnaire, 12 and the Mini Asthma Quality of Life Questionnaire. 55,68 Furthermore, a strong correlation and similar performance were reported between the ATAQ and the ACT at home and in clinical settings (r ϭ Ϫ0.73). 25,69,70 …”
Section: Validitysupporting
confidence: 59%
“…Sullivan et al 68 reported that the costs for uncontrolled asthma, as indicated by the ATAQ score, were more than double those with scores indicating controlled asthma. Also, a higher ATAQ score (more control problems) was associated with lower quality of life in subjects with asthma, indicated by generic and diseasespecific quality of life measures, such as the SF-36, the standardized version of the Asthma Quality of Life Questionnaire, 12 and the Mini Asthma Quality of Life Questionnaire.…”
Section: Validitymentioning
confidence: 99%
“…As a consequence of the above-mentioned differences, determinants and clinical correlates of control and severity may not be identical: for instance, body mass index and obesity are associated with control and quality of life but not with severity (13,14); conversely, tobacco smoking is associated with both poorer control and increased severity (15,16), although this relationship was not significant in the study by Sullivan et al (2). In addition, for patients with a N. Roche 1 , P. Godard given level of severity, control is an additional contributor to quality of life (17).…”
contrasting
confidence: 44%
“…Data presented by Sullivan et al in this issue of Allergy show that patients with severe asthma are frequently uncontrolled, which increases direct and indirect costs of the disease (2). Such results are not really surprising, but they are strengthened by the large scale of the study, which allows quantifying differences more reliably.…”
Section: Control Of Asthma: What Is the Target?mentioning
confidence: 54%
“…School aged children had a higher risk of INS, as allergic asthma is more prevalent in school-aged children, the higher prevalence of INS seen in this age group was therefore consistent with an association between INS and allergic asthma. In addition, we also found children with more asthma-related visits per year had greater risk of INS, which may reflect the association between INS risk and uncontrolled airway inflammation, more severe and persistent phenotype of asthma or more environmental triggers, such as allergen exposure or respiratory virus in asthma children (25,26). Moreover, greater risk of INS was observed within the first 5.5 y after asthma diagnosis.…”
mentioning
confidence: 69%